Indian Statistical Institute Planning Division Working Papers No. 1 to 25 - Planning Commission (Planning Commission, 1954)
The present study aims to show the essential stages of reasoning necessary to follow for a rational elaboration of a plan for economic development. Before passing to the 9 essential point, it is indispensable to specify what will be the approach, from an institutional viewpoint, toward the problem of elaboration of a five-year plan
Studies Relating to Planning for National Development
Government of India Planning Commission
Keywords: National income and investments; Utilisation of the investments funds; Distribution of investments funds within the branches J and C; Method of balances and choice of the desired technique; Investment balance; Composition of the working population; Assumed distribution of investments by branch; Capital intensity’-' in certain branches; Evolution of national income and its composition; Fundamental aspects of financing the investments